Government Liquidity Placement and Bank Financial Performance: Evidence from Indonesian State-Owned Banks - Dadang, Agus (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2026)
This study examines the relationship of government liquidity placements on the financial performance of state-owned banks (SOEs) in Indonesia during the post-pandemic economic normalization period. Although government funds are intended to enhance intermediation capacity and financial system stability, empirical evidence regarding their relationship on bank profitability remains limited. This study employs a quantitative research design using panel data regression with a fixed effects model (FEM). The analysis is conducted on four major state-owned banks over the period 2020–2024. The model controls for bank-specific variables, including the loan-to-deposit ratio (LDR), non-performing loans (NPL), operational efficiency (BOPO), and third-party funds (DPF). The results indicate that the direct relationship of fund placements on return on assets (ROA) is weak, while net interest margin (NIM) declines significantly, reflecting a trade-off between additional liquidity and interest income. However, the lagged relationship on ROA is positive and marginally significant, suggesting that banks require time to channel liquidity into productive lending. This study provides empirical contributions to the understanding of government liquidity dynamics in state-owned banks and their implications for managerial decision-making and fiscal policy.